Redistribution of reactive nitrogen in the Arctic lower stratosphere in the 1999/2000 winter - Koike, M.; Kondo, Y.; Takegawa, N.; Lefèvre, Franck; Ikeda, H.; Irie, H.; Hunton, H. D. E.; Viggiano, A. A.; Miller, T. M.; Ballenthin, J. O.; Sachse, G. W.; Anderson, B. E.; et al. (Journal of Geophysical Research, 2002)
International audience Total reactive nitrogen (NO y ) in the Arctic lower stratosphere was measured from the NASA DC-8 aircraft during the SAGE III Ozone Loss and Validation Experiment (SOLVE) in the winter of 1999/2000. NO y -N 2 O correlations obtained at altitudes of 10-12.5 km in December 1999 and January 2000 are comparable to the reported reference correlation established using the MkIV balloon measurements made during SOLVE prior to the onset of denitrification. Between late February and mid-March, NO y values obtained from the DC-8 were systematically higher than those observed in December and January by up to 1 part per billion by volume, although a compact correlation between NO y and N 2 O was maintained. Greater increases in NO y were generally observed in air masses with lower N 2 O values. The daily minimum temperatures at 450-500 K potential temperature (∼20-22 km) in the Arctic fell below the ice saturation temperature between late December and mid-January. Correspondingly, intense denitrification and nitrified air masses were observed from the ER-2 at 17-21 km and below 18 km, respectively, in January and March. The increases in NO y observed from the DC-8 in late February/March indicate that influence from nitrification extended as low as 10-12.5 km over a wide area by that time. We show in this paper that the vertical structure of the temperature field during the winter was a critical factor in determining the vertical extent of the NO y redistribution. Results from the Reactive Processes Ruling the Ozone Budget in the Stratosphere (REPROBUS) three-dimensional chemistry transport model, which reproduced the observed general features only when the NO y redistribution process is included, are also presented.